Comparison of physicochemical characteristics between white-belly and white-core rice grains. (May 2016) - Xi, Min; Zhao, Yanling; Lin, Zhaomiao; Zhang, Xincheng; Ding, Chengqiang; Tang, She; Liu, Zhenghui; Wang, Shaohua; Ding, Yanfeng
Abstract: Using white-belly and white-core mutants of a japonica rice cultivar Wuyujing3, this study was conducted to compare the physicochemical properties of grains differing in chalkiness type. Chalky grains were larger in length, width, and thickness than the translucent grains, and consequently had higher weight. The notable differences were observed for chemical compositions, with chalky grains showing lower contents of starch and protein than the translucent. Similar trends were noted in the majority of the 17 amino acids examined and contents of manganese (Mn), potassium (K) and magnesium (Mg), suggesting the important role of storage compounds in chalkiness formation. White-belly grains differed from white-core grains in chemical components, with the former having higher amylose contents and lower Zn content. Additionally, white-core grains exhibited markedly lower contents of amino acids derived from oxaloacetate and phosphoenolpyruvate like phenylalanine, aspartate and threonine. However, no noticeable differences were detected between white-belly and translucent grains. Our results indicate different underlying mechanisms of white-belly and white-core, suggesting the necessity of comparing white-belly and white-core in the studies on chalkiness. In addition, future study should focus on interpreting the active role of protein accumulation in chalkiness formation from perspective of interactions of carbon and nitrogen metabolism. Highlights: We compared physicochemical properties of white-belly and white-core grains. Notable differences were observed between chalky and translucent grains. Chalky grains showed lower levels of starch, protein, the majority of 17 amino acids. White-belly grains had higher amylose content and lower Zn content. White-core grains exhibited markedly lower contents of amino acids derived form oxaloacetate/phosphoenolpyruvate.